2015
DOI: 10.1189/jlb.3ru0115-021r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammation by cannabinoids, the endocannabinoids 2-arachidonoyl-glycerol and arachidonoyl-ethanolamide, and their metabolites

Abstract: 2-Arachidonoyl-glycerol (2-AG) and arachidonyl-ethanolamide (AEA) are endocannabinoids that have been implicated in many physiologic disorders, including obesity, metabolic syndromes, hepatic diseases, pain, neurologic disorders, and inflammation. Their immunomodulatory effects are numerous and are not always mediated by cannabinoid receptors, reflecting the presence of an arachidonic acid (AA) molecule in their structure, the latter being the precursor of numerous bioactive lipids that are pro- or anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(224 citation statements)
references
References 294 publications
(230 reference statements)
8
204
0
6
Order By: Relevance
“…Since a recent report showed that COX-2 products of AEA exert protective effects against inflammation (Turcotte et al, 2015), we also investigated the role of COX-2 in the mechanism of AEA's protective effects against NLRP3 inflammasome activation and podocyte and glomerular injury from hHcys. The presence of the COX-2 inhibitor CEL attenuated the protective effects of AEA on markers of Hcys-induced NALP3 (nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3) inflammasome activation and injury to cultured podocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a recent report showed that COX-2 products of AEA exert protective effects against inflammation (Turcotte et al, 2015), we also investigated the role of COX-2 in the mechanism of AEA's protective effects against NLRP3 inflammasome activation and podocyte and glomerular injury from hHcys. The presence of the COX-2 inhibitor CEL attenuated the protective effects of AEA on markers of Hcys-induced NALP3 (nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3) inflammasome activation and injury to cultured podocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among endocannabinoids, anandamide (AEA) has been documented to exert anti-inflammatory effects, but it has also been considered as a source of proinflammatory factors (Gatta et al, 2012). AEA can be metabolized by eicosanoid biosynthetic enzymes and therefore its role against inflammation may be associated with effects of its own and its metabolites on different inflammatory pathways (Turcotte et al, 2015). For example, cyclooxygenase-2 (COX-2) inhibition has been reported to block IL-2 release induced by AEA in mouse splenocytes and to prevent transcriptional activity of the IL-12p40 gene induced by AEA (Correa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Биологические эффекты N-АЭА и 2-АГ реа-лизуются после взаимодействия с соответствующими ре-цепторами -СВ1 и СВ2, представляющими собой разновид-ность семейства GPCR. Помимо влияния на воспаление, активация СВ1 и СВ2, расположенных на мембране нейро-нов, способна снижать чувствительность TRPV1, оказывая тем самым анальгетическое и терморегулирующее действие [66,67].…”
Section: эндоканнабиноидыunclassified
“…AEA has been shown to control the cell choice between growth and death, and 2-AG was shown to be a direct substrate of the cyclooxygenase COX and lipoxygenase LOX pathway [9]. Moreover 2-AG and AEA are endocannabinoids that have been implicated in many physiologic disorders, including obesity, metabolic syndromes, hepatic diseases, pain, neurologic disorders, and inflammation [10].…”
Section: Introductionmentioning
confidence: 99%